Jaume Ferrer de Blanes i Les sentencies catòliques del divi poeta Dant. Una mostra de la presència de Dant al renaixement català. - PLLORENÇ, JOSE; BLAT, JOSE (Scripta)
Lord Ferrer (Vidreres, ~ 1445 - Blanes,1529), royal and aristocratic attorney, cosmographer, jewelrer, lapidary, merchant and writer, after all, an honorable Catalan citizen, left early age, at the court of Naples at King Ferdinand's i service. After this eventful Italian journey he went back to Blanes at the Viscount of Cabrera and Bas' service, until he died in the same town in 1529. One of his servants, seventeen years later, published some of the documents which were found scattered in Ferrer's House, Catholic sentences from the divine poet Dante Florentine, compiled by most respectable lord Jaume Ferrer de Blanes, an exemple of the presence of Dante in Catalan Renaissance.